2011
DOI: 10.1007/s00024-011-0384-1
|View full text |Cite
|
Sign up to set email alerts
|

Probability Theory as Logic: Data Assimilation for Multiple Source Reconstruction

Abstract: Probability theory as logic (or Bayesian probability theory) is a rational inferential methodology that provides a natural and logically consistent framework for source reconstruction. This methodology fully utilizes the information provided by a limited number of noisy concentration data obtained from a network of sensors and combines it in a consistent manner with the available prior knowledge (mathematical representation of relevant physical laws), hence providing a rigorous basis for the assimilation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 39 publications
(34 reference statements)
0
29
0
Order By: Relevance
“…In our current formulation, we assume implicitly that the number of localized sources (Ns) is known a priori (viz., Ns is a fixed quantity that does not need to be estimated). The significantly more difficult problem (not considered herein) of the reconstruction of an a priori unknown number of localized sources was studied by Yee [2008Yee [ , 2010 as a generalized parameter estimation problem. Note that in this case, the source parameter vector q consists of the characteristics (e.g., location and emission rate) for each source as well as Ns, and the dimensionality of the source parameter space depends on Ns.…”
Section: Bayesian Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…In our current formulation, we assume implicitly that the number of localized sources (Ns) is known a priori (viz., Ns is a fixed quantity that does not need to be estimated). The significantly more difficult problem (not considered herein) of the reconstruction of an a priori unknown number of localized sources was studied by Yee [2008Yee [ , 2010 as a generalized parameter estimation problem. Note that in this case, the source parameter vector q consists of the characteristics (e.g., location and emission rate) for each source as well as Ns, and the dimensionality of the source parameter space depends on Ns.…”
Section: Bayesian Frameworkmentioning
confidence: 99%
“…Note that in this case, the source parameter vector q consists of the characteristics (e.g., location and emission rate) for each source as well as Ns, and the dimensionality of the source parameter space depends on Ns. To address this problem, Yee [2008Yee [ , 2010 used a reversible jump Markov chain Monte Carlo algorithm to sample from the generalized parameter space, allowing changes in the dimensionality of the model (viz., changes in Ns). An alternative (and arguably simpler) approach to address the problem of an unknown number of sources is to treat the problem as a model selection problem rather than as a generalized parameter estimation problem.…”
Section: Bayesian Frameworkmentioning
confidence: 99%
“…The problem of reconstruction of an unknown number of localized sources using a finite number of noisy concentration measurements is a significantly more difficult problem. A solution for this problem was ISRN Applied Mathematics 3 proposed by Yee 13,14 who approached the problem as a generalized parameter estimation problem in which the number of localized sources, N, in the unknown source distribution was included explicitly in the parameter vector θ, in addition to the usual parameters that characterize each localized source e.g., location, emission rate, source-on time, source-off time .…”
Section: Isrn Applied Mathematicsmentioning
confidence: 99%
“…Furthermore, it was found that the RJMCMC algorithm sampled the parameter space of the unknown source distribution rather inefficiently. To overcome this technical difficulty, Yee 13,14 showed how the RJMCMC algorithm can be combined either with a form of parallel tempering based on a Metropolis-coupled MCMC algorithm 13 or with a simpler and computationally more efficient simulated annealing scheme 14 to improve significantly the sampling efficiency or, mixing rate of the Markov chain in the variable dimension parameter space.…”
Section: Isrn Applied Mathematicsmentioning
confidence: 99%
See 1 more Smart Citation